PENERAPAN REGRESI PROBIT BIVARIAT UNTUK MENDUGA FAKTOR-FAKTOR YANG MEMENGARUHI KELULUSAN MAHASISWA (Studi Kasus: Mahasiswa Fakultas MIPA Unversitas Udayana) - PRADNYANTARI, NI GUSTI KETUT TRISNA; SUKARSA, I KOMANG GDE; SUCIPTAWATI, NI LUH PUTU (E-Jurnal Matematika; Vol 4 No 2 (2015)DO - 10.24843/MTK.2015.v04.i02.p088, 2015)
The aim of this research to estimate the factors that affect students graduation using bivariate probit regression. Bivariate probit regression is a statistical method that involves two response variables which are qualitative and the independent variables are qualitative, quantitative, or a combination of both. In bivariate probit regression model, the result obtained is the probability of the response variable. The result of this research are the factors that affect significantly for students graduation based on study period are majors, sex, and duration of the thesis, while the factors that significantly for students graduation based on GPA are the entry system, duration of the thesis and the number of parents’ dependents.
Keywords: Bivariate Probit Regression, Study Period, Grade Point Average (GPA), Students Graduation